Strategi Pembelajaran PAI Pada Peserta Didik Tuna Grahita Sekolah Dasar Kelas Awal Di Sekolah Dasar Luar Biasa (SDLB) Pembina Tingkat I Cilandak Lebak- Bulus Jakarta Selatan - Rochmah, Siti Khosiah; Sa’diyah, Rika (BELAJEA: Jurnal Pendidikan Islam, 2017)
Abstract: This study aims to find out the learning strategy of PAI in children of Primary Grade Students in SDLB Pembina Level I Cilandak South Jakarta in academic year 2014/2015. The subjects of the study were the students of primary school grade tunagrahita with mild (C) and moderate (C1) tunag category of 42 children. Data collection techniques used in the form of observation, interview and documentation study. Processing and data analysis include reduction, data display, conclusion and verification. Procedure is done by conducting reduction, then hold display of data obtained from field and after conducting processing and observation of result of research, then do conclusion and end with verification to get validity final conclusion. The results showed that PAI learning strategy that includes planning, implementation and evaluation of learning has been done quite well. Learning Planning (curriculum) PAI refers to the general elementary curriculum and has not been modified, substituted or omitted. New curriculum modifications are made on teacher initiative and creativity. Implementation of learning related to objectives, materials, methods, media, and assessment needs to be tailored to the needs and abilities of each child individually because the ability of learners can not be equalized and standardized. Evaluation of learning outcomes both related to the procedures, mechanisms, means and tools used the same as those done in public elementary schools. But there has been a modification on the form of questions, not applied the national exam (UN) but the school exam for final evaluation of the program. Keywords: Students, children of Primary Grade, the learning strategy